Zentrale des Terrors : Prinz-Albrecht-Str. 8 ; das Hauptquartier der Gestapo - Tuchel, Johannes 1957- (Siedler, 1987)
Johannes Tuchel, Reinold Schattenfroh: Zentrale des Terrors. Prinz-Albrecht-Straße 8. Das Hauptquartier der Gestapo. Siedler Verlag, Berlin 1987. 320 Seiten, Abbildungen, 29,80 Mark